Laser-Induced and MOF-Derived Metal Oxide/Carbon Composite for Synergistically Improved Ethanol Sensing at Room temperature - Lim, Hyeongtae; Kwon, Hyeokjin; Kang, Hongki; Jang, Jae Eun; Kwon, Hyuk‑Jun (Nano-Micro Letters, 2024)
Advancements in sensor technology have significantly enhanced atmospheric monitoring. Notably, metal oxide and carbon (MOx/C) hybrids have gained attention for their exceptional sensitivity and room-temperature sensing performance. However, previous methods of synthesizing MOx/C composites suffer from problems, including inhomogeneity, aggregation, and challenges in micropatterning. Herein, we introduce a refined method that employs a metal–organic framework (MOF) as a precursor combined with direct laser writing. The inherent structure of MOFs ensures a uniform distribution of metal ions and organic linkers, yielding homogeneous MOx/C structures. The laser processing facilitates precise micropatterning (< 2 μm, comparable to typical photolithography) of the MOx/C crystals. The optimized MOF-derived MOx/C sensor rapidly detected ethanol gas even at room temperature (105 and 18 s for response and recovery, respectively), with a broad range of sensing performance from 170 to 3,400 ppm and a high response value of up to 3,500%. Additionally, this sensor exhibited enhanced stability and thermal resilience compared to previous MOF-based counterparts. This research opens up promising avenues for practical applications in MOF-derived sensing devices. Highlights: 1 Metal oxide and carbon hybrids (MOx/C) were micropatterned very rapidly and energy efficiently by direct laser writing. 2 Metal-organic framework was the ideal precursor for fabricating homogeneous MOx/C hybrids due to regularly spaced metal ions and organic ligands. 3 The fabricated sensor not only demonstrated broad-range gas sensing capability for ethanol gas (170-3,400 ppm) but also exhibited exceptional sensitivity, rapid response and recovery, selectivity, linearity, and thermal stability.